Pengaruh Kualitas Pelayanan Akademik terhadap Kepuasan Mahasiswa di Fakultas Keguruan dan Ilmu Pendidikan Universitas Sriwijaya - Nopiyanti, Neka; Sriati, Sriati; Imania, Katriza (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2024)
This research aims to analyze students' perception and expectation values regarding the quality of academic services, the level of student satisfaction with academic services, as well as the cumulative influence of tangibles, reliability, responsiveness, assurance, empathy, and the quality of academic services on student satisfaction at the FKIP Sriwijaya University. The type of this research is descriptive quantitative. Questionnaires, documentation, and literature studies were used in data collection. 360 students from the FKIP Faculty of Education at Sriwijaya University were used as samples in this study. The SPSS 26 software was used in the data analysis of this research. The findings of the study indicate that tangibility and responsiveness do not have a significant effect on Student Satisfaction. Meanwhile, reliability, assurance, empathy, and service quality cumulatively have a significant effect on Student Satisfaction. The service quality variable has an influence of 67.50% on student satisfaction. FKIP Universitas Sriwijaya is expected to continue improving the quality of service and maintaining the already good service to always ensure student satisfaction at FKIP Universitas Sriwijaya.